The shack [compact disc] : music from and inspired by the original motion picture. - McGraw, Tim; Hill, Faith, 1967-; Battistelli, Francesca; Clarkson, Kelly, 1982-; Blacc, Aloe, 1979-; Lecrae (Musician); Bentley, Dierks; Eldredge, Brett, 1986-; Dawson, Devon (Atlantic, 2017)
Featuring previously unreleased music from a wide range of contemporary stars, this soundtrack includes a collaboration from Kelly Clarkson and Aloe Blacc as well as Keep Your Eyes on Me by Faith Hill and Tim McGraw.